Miniestaquia e qualidade de mudas de erva-mate - Pimentel, Nathalia (2016)
The aim of this study were to evaluate the productivity of mini-stumps, the rooting capability of mini-cuttings, and the plantlet quality of holly clones. For rooting, shoots were collected from mini-stumps of four holly clones (10SM07, 06SM17, 06SM15 and 06SM12) in four times during the year. The survival percentage of mini-stumps and the number of mini-cuttings per mini-stump were evaluated. Produced shoots were cut in single-budded mini-cuttings with one leaf reduced to 50% of its original area, which were treated or not with 2000 mg L-1 of indolbutyric acid (IBA). At 30 and 60 days in humid chamber, the percentages of survival, rooting and callus formation in mini-cuttings, and the number and length of roots were evaluated. To determine the optimal time for mini-cuttings rooting, shoots were collected and cut into single-budded ones, which were treated or not with 2000 mg L-1 of IBA and evaluated as to the percentage of rooting, number and length of roots at seven-day intervals from 30 to 107 days of cultivation. To evaluate the quality of the plantlets, mini-cuttings were collected four times during the year and cultivated for 60 days in a humid chamber. Rooted mini-cuttings were transferred to rigid polyethylene tubes of 100 cm³ and polyethylene bags of 500, 1500 and 3000 cm3. At 30, 60, 90 and 120 days of cultivation in green house, the plantlets were evaluated for the percentage of survival, shoot height, stem diameter, ratio of shoot height / stem diameter and number of leaves. At 120 days of cultivation, plantlets were also evaluated for the Dickson quality index, shoot and root dry mass ratio, largest total length, surface area, total volume and number of root tips. The mini-stumps of the four holly clones had high survival, constant production of mini-cuttings by mini-stump of clones 06SM17, 06SM12 and 06SM15 during the four collection times. IBA treatment is not required for rooting mini-cuttings. Rooting of mini-cuttings varied among clones and collection times of the year. The best rooting percentage was gotten at fall and winter for all clones. The clone 06SM15 had the highest rhizogenesis capability in all collection times. The intercept between the daily current increment and the daily medium increment can be used to determine the optimal time for mini-cuttings rooting in humid chamber, which ranged from 58 to 100 days of cultivation, depending on the clone. The best shoot and root dry mass ratio, the largest total length, surface area, and total volume of roots, and Dickson quality index were observed in plantlets produced in July, without differing from those produced in October and January. The polyethylene bags, regardless of the volume (500, 1500 and 3000 cm³), allowed the production of holly plantlets with satisfactory morpho-physiological quality, for both shoot and root system. Holly plantlets can be produced by minicuttings from July to January and grown in polythene bags of 500 cm3.